Effectiveness of psychological crisis interventions during infectious disease outbreaks in low- and middle-income countries: a systematic review of Randomized Control Trials - Biksegn Asrat Yirdaw; Jun Angelo Sunglao; Muhammad Alkasaby; Julian Eaton (Cambridge Prisms: Global Mental Health)
The huge mental health treatment gap in low- and middle-income countries (LMICs) is further exacerbated when infectious disease outbreaks occur. To address the increasing mental health needs during outbreaks, the availability of flexible and efficient mental health interventions is paramount, especially in low-resource settings where outbreaks are more common. Psychological interventions may help to address these mental health needs with efficient implementation costs. However, there is a huge paucity of quality evidence to inform psychosocial interventions during outbreaks. This systematic review sought to update the existing evidence to inform the effectiveness of psychological interventions that addresses mental health issues during outbreaks in LMICs.